KAJIAN FENOMENA VULKANISME DAN DAMPAKNYA PADA KEHIDUPAN SOSIAL MASYARAKAT - Sinaga, Yulistri; Lubis, Aidil Azhary; Ginting, Geby Theresa; Batubara, Mahdiyana Aisyah; Silaban, Marchiana Ivo; Silitonga , Mela Yanna (Lensa: Jurnal Kependidikan Fisika, 2025)
This study explores the multifaceted impacts of volcanic phenomena on the social life of communities in Indonesia, a country situated at the convergence of three major tectonic plates and home to numerous active volcanoes. Utilizing a narrative literature review method, 30 peer-reviewed national and international journal articles published between 2014 and 2024 were analyzed to identify recurring themes and knowledge gaps regarding the socio-economic consequences of volcanic activity. Findings indicate that volcanic eruptions in Indonesia have caused significant disruption to livelihoods, especially in agriculture and tourism, exacerbating economic vulnerability in regions reliant on single-sector economies. Social consequences include mass displacement, forced relocation, and the erosion of communal identity. Health impacts—both physical, such as respiratory illnesses, and psychological, including trauma—are prevalent. Nevertheless, the literature also highlights local resilience through adaptive strategies, strong social capital, and community-based recovery initiatives. Effective disaster mitigation is found to require a combination of scientific early warning systems and the integration of local knowledge. This review underscores the need for participatory policy approaches and continued academic engagement to strengthen disaster preparedness and recovery in vulnerable regions.